Ruang dan Pengasuhan Anak: Perspektif Komunikasi Keluarga - Nikmah Hadiati Salisah (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
Growth and physical, psychological, and spiritual condition of family members is determined by the condition of the house. This paper intends to explore how family members interact specifically with the childcare process with the condition of homes in modest housing locations that have limited facilities and space. By using the phenomenological method it can be seen that with the same size of land but different spatial use and design, interactions and unique results occur in each family studied. The factors of space coloring, furniture selection, sanitation, and function of the space become the determinants in the meaningful process of interaction between parent and child.